Implementasi Kebijakan Jaminan Kesehatan Nasional oleh BPJS Kesehatan di Kota Semarang - Basuki, Eko Wahyu; ., Sulistyowati; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2016)
The provision of health insurance to the people of Indonesia is a form of government to carry out the purposes of the Indonesian nation, one of which is the National Health Insurance policy as a form of good health care to the whole society in Indonesia. For in Semarang itself is still encountered problems in its implementation such as policies which are not effective and the problems of service received from the participants JKN. This study aims to: (1) Explain Implementation The implementation of the National Health Insurance Policy by BPJS in Semarang, (2) Describe the constraints arising from the implementation of the National Health Insurance by BPJS Semarang. The method used in this research is qualitative-descriptive method, with the type of data used are primary data and secondary data uses data collection techniques used were interviews and documentation. The results showed that the implementation of the Implementation of the National Health Insurance by BPJS (Social Security Agency) Health in Semarang has not been realized optimally. This can be seen in still found many obstacles such as lack of awareness of the public about the importance of social security; JKN participants do not understand tiered referral systems and procedures JKN; and regulations that still continues to change. Recommendations can be given is: the government should be able to give cut bureaucracy tiered system because it is perceived complicate the public.